Collective Perception of Anthropic and Extractive Interventions in the Colombian Llanos - Luca Eufemia; Hector Morales; Michelle Bonatti; Maximilian Graser; Marcos Lana; Stefan Sieber (Social Sciences, 2019)
Increasingly, the developmental model of anthropic and extractive interventions is a global concern. Its impacts are challenging not only the precarious equilibrium of natural resources but also the one of local communities and identities. The case of the Colombian Llanos shows how the local culture of the Cultura Llanera (CL) is deep-rooted with natural resources, their use and their management. Throughout the use of a survey based on the Governance Analytical Framework (GAF), this paper presents and discusses shared problems and social norms. The collective perception of local groups shows that the CL, in particular traditional livestock practices in flooded savannahs, is a key element for the sustainable development of the region. Furthermore, it reveals that agricultural and extractive activities, primarily rice and oil, are considered the main threats to both the ecosystem and the protection of the CL.